Diagnostic possibilities in peritonsillar abscess and the significance of transcutaneous ultrasound - Systematic Review of the Literature - Krasuska, Martyna; Nowak, Karolina; Olejarz, Zuzanna; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach, Katarzyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: A peritonsillar abscess is one of the most common complications of tonsillitis, especially among adolescents and young adults. Its diagnosis can pose a challenge, and overlooking it may pose a life-threatening risk. Various diagnostic methods have their advantages and disadvantages. The aim of this publication is to compare and identify the best diagnostic approach currently described in the literature, contributing to improved clinical decision-making and patient outcomes with particular attention to the significance of transcutaneous ultrasound as a diagnostic method. A brief description of state of knowledge: Beyond clinical symptoms imaging options include transcutaneous and oral ultrasound, computed tomography, and magnetic resonance imaging. Ultrasound has been gaining importance in the diagnosis of PTA for an extended period due to its easy accessibility, cost-effectiveness, non-invasiveness and a relatively high anticipated specificity and sensitivity.Simultaneously, the use of CT as a tool in primary diagnosis is being called into question and new proposals for the use of MRI are emerging. Summary: Currently, the use of both intraoral and transcutaneous ultrasound represents the optimal first-line solution in diagnosing peritonsillar abscess. In cases of uncertainty, a more specific diagnostic tool would be MRI, although for various reasons, CT is more commonly chosen.